COVID-19 Pandemic: how we should respond - Charles O C Langoya (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2020)
It is quite interesting to listen to a TED talk given by Bill Gates in 2015 in which he strongly stressed the fact that the next greatest human plight is neither going to be a terrorist attack nor a nuclear war but an infectious agent. He went further mentioning that the infectious agent is likely to be a novel virus that will sweep the globe.